Acute Myocarditis Following Vaccination With the First Dose of the mRNA-1273 Vaccine. (April 2022) - Olagunju, Abdulbaril; Moradi, Ali; Johnson, Benjamin; Lebaron, Zachary; Johnson, Ross; Mehdizadeh, Azar
Viral infections are a common cause of acute myocarditis. However, vaccines including influenza and smallpox have also been rarely implicated. Recently, the coronavirus disease 2019 (COVID-19) vaccines have been associated with acute myocarditis. We describe a case of acute myocarditis in a 19-year-old male 2 days after the initial dose of the COVID-19 mRNA-1273 vaccine. He presented with chest pain radiating to his left arm and bilateral shoulders. COVID, influenza, coxsackie, respiratory syncytial virus polymerase chain reaction (PCR) tests were negative. Electrocardiogram revealed diffuse ST-segment elevation. Initial Troponin was 15.7 ng/mL. A coronary angiogram revealed patent coronary arteries and no wall motion abnormality. A transthoracic echocardiogram showed diffuse hypokinesis with an ejection fraction of 49%. Cardiac magnetic resonance scan was aborted after 2 attempts due to severe claustrophobia. His chest pain resolved following initiation of aspirin, tylenol, colchicine, lisinopril, and metoprolol.